The Charismatic Community: Shi`ite Identity in Early Islam by Maria Massi Dakake (Albany: State University of New York Press, 2007. 300 pages.) (American Journal of Islam and Society, 2008)
A revised and expanded version of a dissertation completed at PrincetonUniversity in 2000, this book describes the emergence of a distinct Shi`itecommunal identity within the larger Islamic community in the periodbetween the First CivilWar (656-61) and the end of the second/eighth century.It draws on the Shi`ite hadith of the Imami (Twelver) tradition in orderto construct a rich picture of the developing Shi`ite community, stressingthe Shi`ites’ ideas about their relationship to the Imam, to each other, andto non-Shi`ites, particularly the Islamic ummah at large.The work is divided into an introduction and three sections of four chapterseach, presenting three major theses. The first four chapters concentrateon the concept of walOEyOE, usually translated as loyalty or allegiance but, asthe author suggests, containing a denotation akin to charisma. She argues thatfrom the beginning, Shi`ism’s crucial characteristic was allegiance to Ali ibnAbi Talib during the First CivilWar. Even after his assassination and the endof the war, allegiance to his cause remained fundamental and he remained theprimary focus for the Shi`ites’ location of charismatic authority ...